2015
DOI: 10.1016/j.ympev.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A survey of transposable element classification systems – A call for a fundamental update to meet the challenge of their diversity and complexity

Abstract: The increase of publicly available sequencing data has allowed for rapid progress in our understanding of genome composition. As new information becomes available we should constantly be updating and reanalyzing existing and newly acquired data. In this report we focus on transposable elements (TEs) which make up a significant portion of nearly all sequenced genomes. Our ability to accurately identify and classify these sequences is critical to understanding their impact on host genomes. At the same time, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 133 publications
0
135
0
Order By: Relevance
“…Recently, we proposed that this definition needs to be broadened to "TEs are discrete segments of DNA capable of moving within a host genome from one chromosome or plasmid location to another, or between hosts by using parasitic vectors that they use for lateral transfers." 3 An important aspect of this definition is that it includes mobile DNA sequences that are primarily maintained by vertical transmission as copies integrated into the chromosomes or plasmids of their hosts. Therefore, according to this definition, while viruses, phages, and integrative conjugative elements (ICE) have similar features to TEs, they are not considered to be TEs because they are able to move between hosts independently of transmission vectors.…”
Section: A Definition Of Tesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we proposed that this definition needs to be broadened to "TEs are discrete segments of DNA capable of moving within a host genome from one chromosome or plasmid location to another, or between hosts by using parasitic vectors that they use for lateral transfers." 3 An important aspect of this definition is that it includes mobile DNA sequences that are primarily maintained by vertical transmission as copies integrated into the chromosomes or plasmids of their hosts. Therefore, according to this definition, while viruses, phages, and integrative conjugative elements (ICE) have similar features to TEs, they are not considered to be TEs because they are able to move between hosts independently of transmission vectors.…”
Section: A Definition Of Tesmentioning
confidence: 99%
“…Based on out findings we concluded that 1) the basal dichotomy view of the TE world advocated by Finnegan is no longer justified by modern science, 2) the Curcio and Derbyshire view appears to us to fit the current science best, but requires careful attention to evolutionary convergences at the molecular level, and 3) the addition of several new TE classes and orders are necessary to keep up with recent discoveries in this field. 3 In Table 1 we outline our proposal for a new taxonomic scheme which has the advantage of allowing the integrating new classes, new orders and new-families, such as the recently described Casposons. 26,27 However, using the same standards as we have applied to previous taxonomic proposal we recognize that our scheme is deficient in several respects.…”
Section: Rationale For Revisiting the Taxonomy Of Tesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such community efforts of standardization should also take into account suggestions for a revised classification system, one which better incorporates the diversity of archaeal, bacterial and eukaryotic forms of mobile genetic elements, and based more upon the divergent phylogenetic lineages of these elements (Piégu et al 2015).…”
mentioning
confidence: 99%